(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2013)
Nutrition is a Basic human need .It is essential for physiological homeostasis & growth. But unfortunately it remains unmet for vast number of children. These children fail to achieve their full developmental potential. Growth assessment is the best indicator to see the health & nutritional status of children. Growth retardation is a constant feature of undernutrition. An observational study was conducted to see the nutritional status on 100 under 5 children of low privileged society following inclusion & exclusion criteria. Their height, weight, skin fold thickness were measured. Their weight for age (measures of underweight), height for age (measures of stunting) & weight for height (Measures of wasting) were assessed. Z scores of weight for age (underweight), height for age (stunting) & Weight for height (wasting) were also assessed. Among them 32 subjects were moderately & 36 were severely undernourished according to reference of WHO. 32 subjects were within the normal range of growth curve according to WHO/NCHS standard. Severely undernourished children were of younger age group and their heights (in cm) were significantly low comparing to normal children, though there was no significant difference in their weight. Except weight for height (wasting) in moderately undernourished children all measurements were significantly lower (p value<0.001) both in moderate & severe undernourished group in comparison to normal children. Serum total protein, albumin & globulin level of all the children were within normal range. This study concludes that about 2/3 of under 5 children suffer from moderate to severe undernutrition in low privileged people in our society. They are underweight & suffer from wasting & stunting from the early childhood. JCMCTA 2013; 24 (1):50-52